2021
DOI: 10.1007/s10067-021-05833-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hospitalization for COVID-19 in patients with autoimmune rheumatic diseases: results from a community cohort follow-up

Abstract: Objective The identification of risk factors for COVID-19 adverse course in autoimmune rheumatic diseases (ARDs) is of the utmost importance when approaching patient management; however, data are scarce in relation to the Latin American population. The objective of this study was to determine predictors of hospitalization for COVID-19 patients from an ARD community cohort. Methods A real setting longitudinal study (March to November 2020) in an ARD community cohort was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Early COVID-19 testing and diagnosis can ensure timely treatment with appropriate therapies including mAb, antivirals, and steroids, which can improve prognosis ( 9, 10 ). While we do not have treatment data, our findings are consistent with previous studies that support early diagnosis and hospitalization of COVID-19 patients to prevent severe outcomes ( 1, 11 ).…”
Section: Discussionsupporting
confidence: 91%
“…Early COVID-19 testing and diagnosis can ensure timely treatment with appropriate therapies including mAb, antivirals, and steroids, which can improve prognosis ( 9, 10 ). While we do not have treatment data, our findings are consistent with previous studies that support early diagnosis and hospitalization of COVID-19 patients to prevent severe outcomes ( 1, 11 ).…”
Section: Discussionsupporting
confidence: 91%
“…The impact of COVID‐19 in patients with autoimmune rheumatic diseases (ARDs) during the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic remains a major concern, especially in systemic lupus erythematosus (SLE). Data are still controversial, with some studies showing that the number of organs involved, disease activity, and ARD itself are associated with COVID‐19 poor outcome (1–3). In contrast, other studies have not confirmed this worse prognosis and have even suggested a lower risk of developing severe COVID‐19 in these patients (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Informal work is much more common in populations with lower socioeconomic status, and social support for these groups was insufficient (60). Since this population had limited in-person and virtual health care access, their diagnosis was usually delayed, portending poorer outcomes (61). Moreover, social media networks were not helpful vehicles for educational outreach in these populations (62), creating barriers to disseminating COVID-19-related information and other information during the pandemic.…”
Section: Latin Americamentioning
confidence: 99%